Occurrence and Survival of Livestock-Associated MRSA in Pig Manure and on Agriculture Fields - Lӕrke Boye Astrup; Julie Elvekjӕr Hansen; Karl Pedersen (MDPI AG, 2021)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is widespread in European pig production, and an increasing number of humans attract infections with this bacterium. Although most infections occur in humans with direct livestock contact, an increasing number of infections occur in humans without any established livestock contact. There have been speculations that at least some of these infections may be connected to the exposure of liquid pig manure for example spread as fertilizers. The present study therefore undertook to measure the presence of LA-MRSA in liquid pig manure and on the surface of soils fertilized with liquid manure and investigate the survival of the bacterium in manure. The results showed that LA-MRSA could be detected in 7 out of 20 liquid manure samples and in 12 out of 186 soil samples. However, the bacterium was not more frequently detected in samples collected after compared to before the spreading of liquid manure on the fields, thus suggesting that other sources of LA-MRSA on agriculture fields likely exist. The decimation time in liquid manure was >32 days at 5 °C in vitro but decreased with increasing temperature. Based on these results, liquid manure does not appear to be an important risk factor for human exposure to LA-MRSA.